BEKATUL BERAS MERAH SEBAGAI SALAH SATU ALTERNATIF SUMBER ANTIOKSIDAN - Wulandari, Putu Adiyasi; Suter, I Ketut; Putra, I Nengah Kencana (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 1 No 1 (2012): Jurnal ITEPA)
Red rice bran is a waste of cendana red rice mill which is widely available in Tabanan regency, Bali. Red rice bran which produced rarely used as feed products. The red rice bran has good nutrition such as anthocyanins, phenolics and antioxidant activity respectively 109.33 mg/100 g rice bran, rice bran 4.38 mg/100 g, and 88.10%. Based on the nutrient content and the high antioxidant activity showed that the red rice bran has great potential to be used as functional foods
Keywords: red rice bran, anthocyanins, antioxidant activity